EVALUATION OF ONLINE LEARNING IN AUTOMOTIVE PRODUCTIVE SUBJECTS IN THE COVID-19 PANDEMI TIME AT KARSA MULYA VOCATIONAL SCHOOL, PALANGKA RAYA - Meiharani, Rizki; Vontas Alfenny Nahan (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2023)
The Covid-19 pandemic has had an impact on various aspects of human life, including education. During the pandemic, face-to-face learning in classes was closed indefinitely. Therefore, in order for the learning process to continue, distance learning devices (PJJ) are needed. The learning process is carried out by students from home through online/distance learning which is carried out to provide a meaningful learning experience for students, without being burdened by the demands of completing all curriculum achievements to improve the competence of automotive expertise in SMK. This study aims to evaluate online learning carried out by students of SMK Karsa Mulya Palangka Raya using the Context, Input, Process, Product (CIPP) evaluation model. This study used a quantative data collection method that was described descriptively. Data was collected through the distribution of questionnaires to class XII Automotive students at SMK Karsa Mulya Palangka Raya. The results of this study stated that the implementation of Online Learning in the school was quite effective with details of the percentage score of online learning activities: (1) context aspect of 67.51%, (2) input aspect of 61.54%, (3) process aspect of 69.81%, and (4) product aspect of 46.54%. Percentage score Online learning media: (1) context aspect of 54.84%, (2) input aspect of 69.35%, (3) process aspect of 68.18%, and (4) product aspect of 61.09%. Based on the results of the analysis, it shows that the implementation of online learning at SMK Karsa Mulya Palangka Raya is quite effective in organizing online learning in terms of learning activities from the perspective of students and online learning media during the Covid-19 pandemic. This research contribution can be a reference for other educational institutions in distance learning, especially vocational schools majoring in automotive.